Assessment the sanitary-hygienic conditions of workplace air in chemical productions of petrochemical industry in Eastern Siberia - N. A. Taranenko; N. M. Meshchakova; S. F. Shayakhmetov (Acta Biomedica Scientifica)
The article presents sanitary-hygienic assessment of the state of air environment of chemical industries of Eastern Siberia of production of methyl alcohol and methylamines, butyl alcohol by oxosynthesis, methyl-tert-butyl ether (MTBE). Productions use continuous production cycles with high degree of automation and mechanization of laborintensive operations. Retrospective study of work area of these productions for 10-year period showed absence of excess of occupational exposure limit of average annual concentration of repugnant substances (methanol, carbonic oxide, methylamines, butanols, MTBE, aliphatic hydrocarbons С1-С10 et al.). Also significant tendency for its decrease during the period of monitoring was registered, that is connected with introduction of organizational-technical and hygienic measures conductive to the sanitation of working conditions on studied productions. Researches conducted at the present day testify to the persistent influence on the employees of the complex of chemical compounds in low concentrations. Nevertheless despite parameters of industrial environment meet hygienic requirements it's necessary to take into account combined influence of risk factors on the employees for prevention occupational diseases.